The Role of The Parents in Educating Gadget Generation - Yudha, Chrisnaji Banindra; Iriansyah, Herinto Sidik; Herzamzam, Dyah Anungrat (Universitas Sebelas Maret, 2019)
Gadget has been familiar in Indonesian area. The gadget in this article is a child who was born and grow thrive on the sophistication of technology. A gadget in the intent is handphone that can be conection on the internet network. The user of gadget ranging from the age of two years to the oldman. The focus of the study in article is users gadget 7 on 13 years or the age of elementary school. The problem is a lock of control employing gadget that is not tarred filter carefully. The child interaction with internet will open the actual unorthodox to open at the age. Ironically gadget become a means of some parents to calm her certain conditions, an example when the child crying, parents shopping at shopping canters, when gathered gathering and the offers. So in the study needed to parents in educating children aged elementary school the use of gadget.